Proceso de atención de enfermería en paciente de 2 años de edad con parálisis cerebral infantil. - Baque Parrales, Emily Denisse (2020)
The present work is a contribution to the field of health where it seeks to demonstrate the theoretical-practical knowledge acquired through the nursing care process, to act efficiently in the implementation of the care necessary to limit the present damage, in In the following clinical case, we have a 2-year-old female patient who comes to the health center for check-ups to assess her current state of health regarding her childhood cerebral palsy. This disorder is an irreversible disability, caused by the poor development or injury of certain areas of the brain that limits the motor skills and communication of those who suffer from it caused by multiple factors depending on the degree of involvement and extent of injury to the brain in which the signs and symptoms may appear before two years of life, it can be generated during pregnancy, occasionally during labor or immediately after birth, according to the stage in which the damage has occurred; they can be prenatal, perinatal or postnatal, in where it constitutes a problem of the first magnitude due to the disability it associates, chronicity and the medical and educational implications.